(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: Calcium channel blockers are amongst the commonly used drugs in the treatment of cardiovascular disorders. They produce their action by blocking voltage regulated calcium channels. Methodolgy: Present study evaluated the effects of three structurally dissimilar calcium channel blockers Nitrendipine (a dihydropyridine) in a single dose of 10 mg and 20 mg, Diltiazem (a benzothiazepine) in a single dose of 30 mg and 60 mg and Verapamil (a phenylalkylamine) in a single dose of 40 mg and 80 mg on psychomotor performance in human volunteers. For evaluation of psychomotor performance, the tests used were arithmetic ability, verbal learning, letter cancellation, digit symbol substitution and card sorting test. Results: Nitrendipine both in low dose (10mg) and high dose (20mg) as well as Diltiazem in high dose (60mg) and Verapamil in high dose (80mg) were found to impair the psychomotor performance in human volunteers to a statistically significant extent in all the tests employed except letter cancellation test. Whereas Diltiazem in low dose (30mg) and Verapamil in low dose (40mg) showed statistically significant impairment of psychomotor performance using arithmetic ability, verbal learning, and digit symbol substitution test. Conclusion: Thus calcium channel blockers namely Nitrendipine, Diltiazem and Verapamil significantly impaired the psychomotor performance of human volunteers in our study. DOI: http://dx.doi.org/10.3329/bjms.v12i1.11534 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.43-48